Lipid Signaling in Plants - Munnik, Teun.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book highlights the current status of plant lipid signaling. Written by leading researchers in the field, the chapters include detailed information on the measurement, regulation and function of phospholipases, lipid kinases, lipid phosphatases, inositolpolyphosphates, polyphosphoinositides, phosphatidic acid and additional lipid signals, e.g. oxylipins, NAPE and sphingolipids. Together, it represents a timely and comprehensive update of the rapidly expanding field of lipid signaling in plant stress and development.
Phospholipases -- Phospholipase A in Plant Signal Transduction -- The Emerging Roles of Phospholipase C in Plant Growth and Development -- Plant Phospholipase D -- Kinases -- Phosphatidylinositol 4-Phosphate is Required for Tip Growth in Arabidopsis thaliana -- PIP-Kinases as Key Regulators of Plant Function -- Plant Phosphatidylinositol 3-Kinase -- Diacylglycerol Kinase -- Phosphatases -- Signaling and the Polyphosphoinositide Phosphatases from Plants -- Phosphatidic Acid Phosphatases in Seed Plants -- PPI Metabolism -- InsP3 in Plant Cells -- Inositol Polyphosphates and Kinases -- Phosphoinositides and Plant Cell Wall Synthesis -- Imaging Lipids in Living Plants -- PA Signaling -- Phosphatidic Acid: An Electrostatic/Hydrogen-Bond Switch? -- Nitric Oxide and Phosphatidic Acid Signaling in Plants -- 3-Phosphoinositide-Dependent Protein Kinase is a Switchboard from Signaling Lipids to Protein Phosphorylation Cascades -- Diacylglycerol Pyrophosphate, A Novel Plant Signaling Lipid -- Additional Lipid Signals -- Oxylipin Signaling and Plant Growth -- Fatty Acid Amide Hydrolase and the Metabolism of N-Acylethanolamine Lipid Mediators in Plants -- Sphingolipid Signaling in Plants.
Keywords: Life sciences; Biochemistry; Cytology; Botany; Plant breeding; Plant physiology; Life Sciences; Plant Biochemistry; Plant Genetics & Genomics; Plant Physiology; Plant Sciences; Cell Biology